Feasibility Analysis of Durian Cultivation Business (Durio Xinethius) and Economic Benefits for Durian Farmers in Bontang, East Kalimantan - Rediyono Rediyono; Hardika Muhammad Fatih; Didik Cahyono (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Durian cultivation is a high-value agricultural business with the potential to improve farmers' welfare. However, this business requires a comprehensive economic feasibility analysis because it is a medium- to long-term investment. This study aims to analyze the feasibility of durian cultivation and its contribution to the economic conditions of farmers in Bontang City, East Kalimantan. The research method used was a descriptive quantitative approach with a census method of 19 durian farmers. Data were collected through structured interviews, field observations, and documentation, then analyzed using cost, revenue, income, and business feasibility analysis. The results showed that durian cultivation is economically feasible with revenues far exceeding production costs, including during the pre-production period before the plants bear fruit.